Artificial neural networks and image interpretation: a ghost in the machine. - Scott JA (Seminars in Ultrasound, CT & MRI, 2004)
The artificial neural network (ANN) is a non-algorithmic parallel processing device modeled after human cerebral architecture. ANNs can be readily simulated on a digital computer and have the potential for significant diagnostic application in both image- and non-imagebased medical diagnosis. This paper briefly discusses the operation of ANNs, differences between these and more traditional problem solving methods, and some diagnostic imaging problems amenable to their application. Copyright © 2004 by Elsevier Science (USA).